Correlation Between Knowledge and Attitude to Oral Hygiene Management Behavior on Nasopharyngeal Cancer Patients Undergoing Radiation Therapy - Rita Anita; Widanarti Setyaningsih; Sari Narulita (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: In nasopharyngeal cancer, radiotherapy is known as the treatment of choice by utilizing ionized radiation to eradicate all cancer cells in the nasopharynx and their metastases in the lymph nodes. This study aimed to determine the correlation between knowledge and attitude on oral hygiene management behavior among nasopharyngeal cancer patients undergoing radiation therapy in Jakarta. Methods: A descriptive correlative with a cross-sectional. Using total sampling on 45 respondents at Radiotherapy Installation at Dharmais Cancer Hospital. The measurement using questionnaire to determine the correlation between knowledge and attitudes to oral hygiene management behavior on nasopharyngeal cancer patients. Fisher Exact Test was used for univariate and bivariate analysis.  Results: Up to 68.9% respondents had a good level of knowledge, while 77.8% respondents had a positive attitude and also had good behavior on oral hygiene management. Fisher Exact Test showed a correlation between knowledge on oral hygiene management behavior n nasopharyngeal cancer patients with radiation with a p–value = 0.002. The results also show a significant correlation between attitudes on oral hygiene management behavior in nasopharyngeal cancer patients with radiation with a p–value = 0.000. Conclusion: Patients with good knowledge and positive attitudes have good oral hygiene behavior, whereas patients with poor knowledge and negative attitudes will behave with poor oral hygiene management. Increase the knowledge, attitudes, and behavior of oral hygiene management of NPC patients who will undergo radiation through the provision of continuing education from the beginning to the end of radiation. Provide educational media so that patients achieve a better understanding.